Pengaruh Bauran Pemasaran Terhadap Volume Penjualan Produk Ayam Pedaging Di Kota Makassar - Andi Faisal Suddin (State Islamic University (UIN) Alauddin, 2013)
This study aimed to analyze the influence of the marketing mix includes product, price and distribution to sales volume broiler products in some traditional markets in the city of Makassar (central market, terong market, pa'baeng-Baeng market, panampu market and daya market). The research design using cross sectional study with a sample of 100 people. Sampling is done exchautic sampling. The data was collected through observations, interviews and questionnaires. Data were analyzed using chi-square test followed by linear regression to determine the independent variables are the most influential. The results showed that there are three variables that influence of marketing mix of product (p = 0.032), price (p = 0.001), distribution (p = 0.020). Variables that most strongly influence the effectiveness of the sales are priced with sig (p) = 0.010 and (Beta = 0.282). Traders expected the broiler products further enhance the marketing mix of the aspects (product, price and distribution) that can be improved chicken sales. Traders need to do a more careful consideration such as the determination of the selling price, the price imposed competitors, and costs incurred with respect to the business of increasing sales. Keywords: Marketing Mix, Volume of Sales.